Full-wave rectification based upon hot-electron thermopower - Wiemann, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, A.; Meier, C. (Applied Physics Letters)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Nonpolar cubic AlGaN/GaN heterojunction field-effect transistor on Ar+ implanted 3C–SiC (001) - Tschumak, E.; Granzner, R.; Lindner, Jörg; Schwierz, F.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (Applied Physics Letters)
A heterojunction field-effect transistor (HFET) was fabricated of nonpolar cubic AlGaN/GaN grown on Ar+ implanted 3C–SiC (001) by molecular beam epitaxy. The device shows a clear field effect at positive bias voltages with V_th=0.6 V. The HFET output characteristics were calculated using ATLAS simulation program. The electron channel at the cubic AlGaN/GaN interface was detected by room temperature capacitance-voltage measurements.

Measurement of effective electron mass in biaxial tensile strained silicon on insulator - Feste, Sebastian F.; Schäpers, Thomas; Buca, Dan; Zhao, Qing Tai; Knoch, Joachim; Bouhassoune, Mohammed; Schindlmayr, Arno; Mantl, Siegfried (Applied Physics Letters)
We present measurements of the effective electron mass in biaxial tensile strained silicon on insulator (SSOI) material with 1.2 GPa stress and in unstrained SOI. Hall-bar metal oxide semiconductor field effect transistors on 60 nm SSOI and SOI were fabricated and Shubnikov–de Haas oscillations in the temperature range of T=0.4–4 K for magnetic fields of B=0–10 T were measured. The effective electron mass in SSOI and SOI samples was determined as mt=(0.20±0.01)m0. This result is in excellent agreement with first-principles calculations of the effective electron mass in the presence of strain.

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Ellipsoidal InAs quantum dots observed by cross-sectional scanning tunneling microscopy - Blokland, J. H.; Bozkurt, M.; Ulloa, J. M.; Reuter, Dirk; Wieck, A. D.; Koenraad, P. M.; Christianen, P. C. M.; Maan, J. C. (Applied Physics Letters)

Using a two-dimensional electron gas to study nonequilibrium tunneling dynamics and charge storage in self-assembled quantum dots - Marquardt, B.; Geller, M.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Probing the band structure of InAs∕GaAs quantum dots by capacitance-voltage and photoluminescence spectroscopy - Lei, W.; Offer, M.; Lorke, A.; Notthoff, C.; Meier, Cedrik; Wibbelhoff, O.; Wieck, A. D. (Applied Physics Letters)

Magnetotransport in Gd-implanted wurtzite GaN∕AlxGa1−xN high electron mobility transistor structures - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Cordier, Y.; Wieck, A. D. (Applied Physics Letters)

Coherent spin dynamics in Permalloy-GaAs hybrids at room temperature - Hohage, P. E.; Nannen, J.; Halm, S.; Bacher, G.; Wahle, M.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electrical detection of photoinduced spins both at room temperature and in remanence - Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Wende, H.; Petracic, O.; Westerholt, K. (Applied Physics Letters)

Room temperature electrical spin injection in remanence - Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Lo, F.-Y.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Wende, H.; Keune, W.; Petracic, O.; Westerholt, K. (Applied Physics Letters)

Submicrometer periodic patterns fixed by photopolymerization of dissipative structures - Hoischen, A.; Benning, S. A.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Influence of doping on the photorefractive properties of a polymer-dispersed liquid crystal - Redler, Andreas; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Single-photon level ultrafast all-optical switching - Han, Xiao-Feng; Weng, Yu-Xiang; Wang, Rui; Chen, Xi-Hao; Luo, Kai Hong; Wu, Ling-An; Zhao, Jimin (Applied Physics Letters)

Enhanced transmission of periodic, quasiperiodic, and random nanoaperture arrays - Rockstuhl, Carsten; Lederer, Falk; Zentgraf, Thomas; Giessen, Harald (Applied Physics Letters)

Technique for tilting GaAs photonic crystal nanocavities out of plane - Meier, Cedrik; Hennessy, Kevin (Applied Physics Letters)

Magnetic and structural properties of Gd-implanted zinc-blende GaN - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Wieck, A. D.; Ney, V.; Kammermeier, T.; Ney, A.; Schörmann, J.; Potthast, S.; As, D. J.; Lischka, K. (Applied Physics Letters)